2014
DOI: 10.1080/19315864.2014.930547
|View full text |Cite
|
Sign up to set email alerts
|

Validity Study of the CBCL 6–18 for the Assessment of Emotional Problems in Youth With ASD

Abstract: Youth with autism spectrum disorder (ASD) often present with emotional problems such as anxiety and depression (American Psychiatric Association, 2013). A recent study of the Child Behavior Checklist 6-18 (CBCL; Achenbach & Rescorla, 2001) indicated good sensitivity but relatively low specificity for identifying emotional problems in youth with ASD. The current study examined the extent to which variance in the CBCL's Anxious/Depressed, Withdrawn/Depressed, Internalizing Domain, and Total Problems scales was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 36 publications
1
26
0
Order By: Relevance
“…Because of the use of two age-dependent versions, we used t scores to ensure the comparability of scores. Previous research confirmed the good psychometric properties of the CBCL in ASD samples (Pandolfi et al 2009(Pandolfi et al , 2014.…”
Section: Methodssupporting
confidence: 62%
“…Because of the use of two age-dependent versions, we used t scores to ensure the comparability of scores. Previous research confirmed the good psychometric properties of the CBCL in ASD samples (Pandolfi et al 2009(Pandolfi et al , 2014.…”
Section: Methodssupporting
confidence: 62%
“…This implies that practitioners should be assessing for ED conditions in individuals with ASD. While this may occur upon initial diagnostic assessment routine monitoring for ED through formal screening is important for early identification (see Magyar & Pandolfi, 2012; Pandolfi & Magyar, 2016; Pandolfi, Magyar, & Dill, 2012; and Pandolfi, Magyar, & Norris, 2014). The use of third party report when used as part of a multimethod/informant approach is critical for a couple of reasons (e.g., see Tarbox, La Cava, & Hoang for a discussion on considerations in ASD assessment).…”
mentioning
confidence: 99%
“…The Child Behavior Checklist 6–18 (CBCL; Achenbach & Rescorla (2001) is one widely used screening measure for emotional and behavioral problems (EBP) and was recently evaluated for its potential use in assessing youth with ASD (Pandolfi, Magyar, & Dill, 2012; Pandolfi, Magyar, & Norris, 2014). This norm-referenced caregiver completed questionnaire screens for a wide range of EBP.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Across the studies, a variety of tools were used to assess depressive symptoms. These tools included the Depression Self Rating Scale for Children, (28,48) Kendel's Depressive Symptoms scale, (29,49) Child Behavior Checklist, (30,42) Child Depression Inventory, (31,32,35,41,44,50) Short Mood and Feelings Questionnaire, (34,(36)(37)(38)(39)51) Center for Epidemiological Studies Depression Scale, (33,40,43,45,52,53) Beck Depression Inventory, (47,54) Child Symptom Inventory (55) and Global School-based Student Health Survey Questionnaire. (44,46) Each scale used a continuous score, with higher scores indicating greater depressive symptomology.…”
Section: Resultsmentioning
confidence: 99%